IMPLIKASI YURIDIS REMISI BAGI NARAPIDANA KASUS TINDAK PIDANA KORUPSI (STUDI KASUS DI LEMBAGA PEMASYARAKATAN KELAS IIA MATARAM) - JAUHARI D. KUSUMA; B. FARHANA KURNIA LESTARI (GANEC SWARA, 2023)
This research aims to analyze the regulations for granting remissions to corrupt convicts in the perspective of Law of the Republic of Indonesia Number 22 of 2022 concerning Corrections and to examine how the criteria for granting remissions for prisoners in Corruption Crime cases are regulated according to the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 7 of the Year 2022 Concerning Requirements and Procedures for Implementing the Rights of Prisoners and how to implement Remission for prisoners in Corruption Crime Cases at the Mataram Class II A Correctional Institution. Formulation of the problem; (1) What is the mechanism for granting remission to corrupt convicts according to Law of the Republic of Indonesia Number 22 of 2022 and (2) What are the juridical implications of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 7 of 2022 in fulfilling the right to remission for Corruptor Convicts. This research uses empirical juridical legal research method that focuses on researching applicable laws and regulations and their application in the field. Based on the results of the research conducted, it can be seen that remission is a reduction in the period of serving a sentence given to prisoners and children who meet the requirements specified in the provisions of the regulations per the Law. The conditions for obtaining remission as regulated in Law of the Republic of Indonesia Number 22 of 2022 concerning Corrections are: having good behavior, actively participating in a coaching program, and having demonstrated a reduced level of risk. For Corruption Case Convicts, JC (Justice Collabulator) is no longer required but is still required to pay the fine and/or replacement money in full